Fueling for the field: Nutrition for jumps, throws, and combined events - Sygo, J.; Kendig Glass, A.; Killer, S. C.; Stellingwerff, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Within the sport of athletics (track and field), field events (jumps and throws) differ substantially from track events, both in training demands and in competition format. Combined events (CEs; the seven-event heptathlon and 10-event decathlon) encompass these demands, as well as those from multiple track events, including sprints, hurdles, and middle-distance events. Unlike track events, which rely on a single timed race to determine outcomes, field event athletes must translate speed (forward or rotational) and power into the farthest or highest jump or throw, with the best outcome over multiple (typically at least three, but up to six) attempts. Jumping events, which include the long jump, high jump, triple jump, and pole vault demand extreme technical proficiency, while placing significant asymmetrical neuromuscular (NM) loads on the athlete due to the single-limb dominant nature of these events. The need to jump as high or as far as possible also demands that athletes maintain an optimal body mass (BM) and body composition that maximize their power-weight (power-to-weight) ratio. Throwing events, which include shot put (SP), discus throw, javelin throw (JT), and hammer throw (HT), demand exceptional strength and speed to generate velocity to maximize the throwing distance, and they are typically performed by athletes with a higher relative BM, although this varies by event. Athletes in CE compete over 2 days in multiple events that utilize a range of energy systems, requiring divergent phenotypic adaptations and disparate training modalities.